2020
DOI: 10.1007/s12170-020-00646-4
|View full text |Cite|
|
Sign up to set email alerts
|

Management of the Patient with Heart Failure and an Implantable Pulmonary Artery Hemodynamic Sensor

Abstract: Purpose of Review Heart failure (HF) management guided by hemodynamics obtained from an implantable pulmonary artery pressure (PAP) sensor (CardioMEMS) improves symptoms and reduces HF hospitalizations (HFH). This paper reviews the theoretical basis of pulmonary vascular physiology, summarizes recently published data about CardioMEMS, and provides practical guidelines for patient selection and management. Recent Findings Compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The CardioMEMS™ (CardioMEMS HF System, Abbott, Sylmar, CA) is an implantable wireless sensor placed in the left lower lobe pulmonary artery (through a catheter-delivery system), capable of remotely measuring PAP [18]. It is the only invasive HF remote monitoring sensor with Food and Drug Administration (FDA) approval and European Conformity (CE) mark [19].…”
Section: Cardiomems™ Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…The CardioMEMS™ (CardioMEMS HF System, Abbott, Sylmar, CA) is an implantable wireless sensor placed in the left lower lobe pulmonary artery (through a catheter-delivery system), capable of remotely measuring PAP [18]. It is the only invasive HF remote monitoring sensor with Food and Drug Administration (FDA) approval and European Conformity (CE) mark [19].…”
Section: Cardiomems™ Technologymentioning
confidence: 99%
“…It is the only invasive HF remote monitoring sensor with Food and Drug Administration (FDA) approval and European Conformity (CE) mark [19]. Patients take daily home measurements with an external electronics system and transmit the PAP data wirelessly for clinician review [18,19]. The recent studies showed that the CardioMEMS™ reduced HF hospitalizations and improved quality of life (Table 2) [46][47][48][49][50][51].…”
Section: Cardiomems™ Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…TM may also involve arrhythmia detection using ICD- or CRT-based algorithms or dedicated long-term implanted devices. [ 12 , 27 , 28 , 30 , 31 ]…”
Section: Telemedicine In Heart Failure: Remote Patient Managementmentioning
confidence: 99%
“…A remote pulmonary pressure-guided program usually requires a dedicated nurse or advanced practice provider with experience in heart failure supervised by a cardiologist. Administrative support is necessary for adequate billing to assure the sustainability of the program [76]. Hemodynamic-GUIDEd management of Heart Failure (GUIDE-HF) ongoing trial to evaluate the safety and efficacy of CardioMEMS TM in patients with HF and NYHA II-IV and symptomatic patients with elevated natriuretic peptides without recent heart failure hospitalization [77].…”
Section: Pulmonary Arterial Pressurementioning
confidence: 99%